At the intersection of anger, chronic pain, and the brain: A mini-review. (April 2022) - Yarns, Brandon C.; Cassidy, Justina T.; Jimenez, Amy M.
Abstract: Chronic pain remains one of the most persistent healthcare challenges in the world. To advance pain treatment, experts have recently introduced research-driven subtypes of chronic pain based on proposed underlying mechanisms. Nociplastic pain (e.g., nonspecific chronic low back or fibromyalgia) is one such subtype which may involve a greater etiologic role for brain plasticity, painful emotions induced by life stress and trauma, and unhealthy emotion regulation. In particular, correlational and behavioral data link anger and the ways anger is regulated with the presence and severity of nociplastic pain. Functional neuroimaging studies also suggest nociplastic pain and healthy anger regulation demonstrate inverse patterns of activity in the medial prefrontal cortex and amygdala; thus, improving anger regulation could normalize activity in these regions. In this Mini-Review, we summarize these findings and propose a unified, biobehavioral model called the Anger, Brain, and Nociplastic Pain (AB-NP) Model, which can be tested in future research and may advance pain care by informing new treatments that address anger, anger regulation, and brain plasticity for nociplastic pain. Highlights: Brain plasticity and emotions affect nociplastic pain conditions like fibromyalgia. Anger and its regulation have particularly strong effects on nociplastic pain. Nociplastic pain and anger may have opposite neural correlates. Improving anger regulation could normalize brain activity in nociplastic pain. The Anger-Brain-Nociplastic Pain (ABPN) Model can be tested in future research.